Manajemen Pondok Pesantren Sabiilul Huda dalam Pembentukan Kemandirian Santri di Kota Bandung - Putra, Agung Sembhara; Muhyiddin, Asep (Tadbir: Jurnal Manajemen Dakwah, 2023)
Islamic boarding schools are tertian educational institutions in Indonesia whose existence as centers of Islamic education have a very large role in shaping the character of the Indonesian nation. This paper aims to determine the application of management functions and elements to the Sabiilul Huda Islamic Boarding School as an effort to establish the independence of students with management. The method used in this research is descriptive method, because the main objective of this research is to find out and provide an explanation of the formation of the independence of the students based on management by applying the functions and elements of management to the students. The results of this study show that management in the formation of student independence is implemented by the Sabiilul Huda Islamic Boarding School. Based on these findings it can be concluded that the management of the Sabiilul Huda Islamic Boarding School is in the establishment of independence in order to improve the management function of the Sabiilul Huda Islamic Boarding School. The application of management functions and elements to Islamic boarding schools is an application of science to the reality of the process of achieving goals in the process of self-reliance of students, one of which is carried out at the Sabiilul Huda Islamic Boarding School.